Inorganic electrosynthesis: a green chemical method for tin complexes - Jiménez Pérez, Víctor Manuel; Muñoz Flores, Blanca M.; Kharisov, Boris I.; Hernández Fernández, Eugenio; López Cortina, Susana; Waksman de Torres, Noemí; Ramírez Durón, Rosalba (Dra. Idalia Gómez de la Fuente, 2011)
Sn complexes of the series of bulky amines have been reported by electrochemical oxidation (3 h) of a tin anode in a cell containing methanol solution of the corresponding bulky amine. All were full characterized by 'H and C-NMR, IR and high resolution mass spectrometry. However, all were not enough soluble in organic colvent in order to record its Sn-NMR spectra, this unusual behavior was attributed to the polymeric association thought intermolecular coordination OSn.